2007
DOI: 10.1007/s11517-007-0243-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cerebral autoregulation assessment using chaotic analysis in diabetic autonomic neuropathy

Abstract: Cerebral autoregulation (CA) was assessed by chaotic analysis based on mean arterial blood pressure (MABP) and mean cerebral blood flow velocity (MCBFV) in 19 diabetics with autonomic neuropathy (AN) and 11 age-matched normal subjects. MABP in diabetics dropped significantly in response to tilting (91.6 +/- 14.9 vs. 74.1 +/- 13.4 mmHg, P < 0.05). Valsalva ratio of heart rate was reduced in diabetics compared to normal (1.1 +/- 0.1 vs. 1.5 +/- 0.2, P < 0.05). It indicated AN affects the vasomotor tone of periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…46 One previous study calculating MLE on heart rate variability used 20 000 points, 70 while another study calculating MLE, correlation dimension, and Kolmogorov entropy of cerebral blood flow velocity used 5 to 10 minutes of data with a sampling rate of 60 Hz. 71 An article calculating MLE for postural displacement used 100 seconds of data sampled at 100 Hz. 39 Our time series with 45 000 data points collected over 15 minutes is larger than most previously published series but collected at a slightly slower sampling rate (50 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…46 One previous study calculating MLE on heart rate variability used 20 000 points, 70 while another study calculating MLE, correlation dimension, and Kolmogorov entropy of cerebral blood flow velocity used 5 to 10 minutes of data with a sampling rate of 60 Hz. 71 An article calculating MLE for postural displacement used 100 seconds of data sampled at 100 Hz. 39 Our time series with 45 000 data points collected over 15 minutes is larger than most previously published series but collected at a slightly slower sampling rate (50 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…In a study on traumatic brain injury patients, better reproducibility was shown with MMPF phase compared to ARI [10]. Also non-linear approaches have been tried to evaluate dCA [11, 15], but clear benefits have not been shown yet.…”
Section: Introductionmentioning
confidence: 99%
“…Higher correlation dimension values between ABP and CBFV, lower values of Lyapunov exponent and higher values of Kolmogorov entropy were all found in diabetic subjects with autonomic neuropathy in comparison with normal subjects, Liau et al (2008). Higher correlation dimension values between ABP and CBFV, lower values of Lyapunov exponent and higher values of Kolmogorov entropy were all found in diabetic subjects with autonomic neuropathy in comparison with normal subjects, Liau et al (2008).…”
Section: Diabetesmentioning
confidence: 87%